“Comparative Study of Various Approaches for Solving the Assignment Problem” (International Journal of Food and Nutritional Sciences, 2022)
The Assignment Problem, a fundamental optimization challenge with applications across diverse domains, involves the assignment of a set of tasks to a set of resources in a manner that minimizes a certain objective function. This paper presents a comprehensive comparative study of various approaches employed to tackle the Assignment Problem. The primary objective of this research is to analyze the strengths and weaknesses of different methodologies, providing valuable insights into their applicability and performance characteristics.